2019
DOI: 10.1038/s41598-019-42799-2
|View full text |Cite
|
Sign up to set email alerts
|

Modelling changes in glutathione homeostasis as a function of quinone redox metabolism

Abstract: Redox cycling is an understated mechanism of toxicity associated with a plethora of xenobiotics, responsible for preventing the effective treatment of serious conditions such as malaria and cardiomyopathy. Quinone compounds are notorious redox cyclers, present in drugs such as doxorubicin, which is used to treat a host of human cancers. However, the therapeutic index of doxorubicin is undermined by dose-dependent cardiotoxicity, which may be a function of futile redox cycling. In this study, a doxorubicin-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…3.4.11.2] involved in the Glutathione metabolism; and SF4274, a NAD(P)H dehydrogenase (quinone) [EC:1.6.5.2] involved in Metabolic pathways (Figure 6B). This result correlates with the fact that glutathione and quinone metabolism play a major role in the defense against redox cycling-derived oxidative stress (Kelly et al, 2019), reinforcing the notion that common expression patterns identified in this work correlates with similar protein roles in the cell.…”
Section: Metabolism and Similar Regulationsupporting
confidence: 84%
“…3.4.11.2] involved in the Glutathione metabolism; and SF4274, a NAD(P)H dehydrogenase (quinone) [EC:1.6.5.2] involved in Metabolic pathways (Figure 6B). This result correlates with the fact that glutathione and quinone metabolism play a major role in the defense against redox cycling-derived oxidative stress (Kelly et al, 2019), reinforcing the notion that common expression patterns identified in this work correlates with similar protein roles in the cell.…”
Section: Metabolism and Similar Regulationsupporting
confidence: 84%
“…However, with links between 10 metabolites in 13 reactions simulated using detailed kinetic equations, Reed’s model (available at Biomodels: BIOMD0000000268) is an excellent basis for further development of computer simulations of GSH metabolism for different applications. An interesting example of an extension to Reed’s GSH metabolism model has been presented by Kelly et al, [ 169 ] with the addition of quinone redox metabolism to the GSH model. With this addition, glutathione’s role in mitigating toxicity from quinone-derivatives is combined with its overall kinetics providing a link between glutathione depletion in different compartments with quinone redox.…”
Section: Computer Modeling Of Gsh Metabolismmentioning
confidence: 99%
“…Doxorubicin causes significant dose-dependent cardiotoxicity, possibly due to futile redox cycling. Cellular GSH is a major defense against the redox cycling-derived oxidative stress and therefore a detailed model of glutathione-quinone interplay is of great interest to cancer treatment and analysis of side effects [ 169 ].…”
Section: Computer Modeling Of Gsh Metabolismmentioning
confidence: 99%
“…TNF-α) 25 . As fruti is a quinone compound, which are known inducers of GSH adduct formation and oxidative stress 16,26 , we measured GSH content and ROS production on MCF-7 cells. However, curiously, neither short nor longer incubation times depleted GSH, showing no involvement of cellular death by oxidative stress.…”
Section: Discussionmentioning
confidence: 99%